Teacher Strategy in Repetition on Students' Ability to Memorize Short Verses in Students at MIN 01 Rejang Lebong - Putri Adelia; Idi Warsah; Dewi Purnama Sari (CV Media Inti Teknologi, 2024)
Madrasah Ibtidaiyah Negeri (MIN) 01 Rejang Lebong is an Islamic educational institution that is committed to providing quality Islamic religious education to children. In an effort to improve children's ability to memorize short verses, the use of effective learning methods is the key to success. One of the methods that is often used in learning short verses of the Quran is the repetition method. The purpose of this study is to identify the methods that teachers employ in repetition to help students at MIN 01 Rejang Lebong become better at memorizing brief verses. Descriptive qualitative research methodology is employed. Data was gathered by means of linked document research, interviews, and observation. According to the study's findings, educators employ a range of tactics, such as using engaging instructional materials, a variety of teaching approaches, and suitable motivation and assessment systems. These results can help researchers and educators enhance the efficacy of instruction, particularly when it comes to helping pupils at MIN 01 Rejang Lebong memorize brief poems through repetition. The conclusion of this study is that teachers need to apply various strategies that include regular repetition, in the context of this repetition using the Jama' method, by using repetition can help students enter their memorization into long-term memory, so that their memorization is permanent.